Evaluation Neutrophil Chemotaxis Disfunction to Aggressive and Chronic Periodontitis - Ioana Martu; Maria Ursache; Silvia Martu; Ionut Luchian; Marcel Costuleanu (Romanian Society of Oral Rehabilitation, 2012)
Aim: In this study, we attempted to identify the proteins involved in aggressive periodontitis and chronic periodontitis associated with neutrophil chemotaxis dysfunction. Material and Methods: method were examined in neutrophils from four types of subjects using the real-time polymerase chain reaction: twenty patients suffering from aggressive periodontitis with or without the dysfunction, 15 patients with chronic periodontitis, and 15 controls. A two-dimensional fluorescence difference gel electrophoresis system was used to detect differences in protein expression between neutrophils from four patients suffering from aggressive periodontitis combined with neutrophil chemotaxis dysfunction and those from four controls. Results: Four proteins, displayed a higher protein expression level in the neutrophils from the patients suffering from aggressive periodontitis combined with the neutrophil dysfunction than in those from the control group. The caldesmon mRNA levels in the neutrophils from the patients suffering from aggressive periodontitis combined with the neutrophil dysfunction were high compared with those in the neutrophils from the patients suffering from the other two types of periodontitis and those from the control group. Conclusion: The levels of protein production in neutrophils from aggressive periodontitis patients with the dysfunction were higher than those in neutrophils from the control group. In particular, caldesmon is a candidate marker of aggressive periodontitis combined with neutrophil chemotaxis dysfunction.